(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Epilepsy is an episodic brain dysfunction featured by recurring erratic spontaneous seizures followed by cognitive, social, neurobiological, and psychological consequences. Conventional anti-epileptic drugs are associated with several untoward effects, and hence long-term treatment compliance is a major problem in the management of epilepsy. Herbal drugs have shown promising efficacy as potent anticonvulsants in the past few years. In light of this, the anticonvulsant effect of alcoholic extract of leaves of Helianthus tuberosus (AHT) against maximal electroshock (MES) induced convulsions was investigated. In the present investigation, an indigenous plant, H. tuberosus was studied for its protective effect against maximal electroshock (MES) induced convulsions in Wistar albino rats. The rats were pre-treated with different doses (100, 200, 400 mg/kg) of alcoholic extract of leaves of H. tuberosus for 14 days, and then, they were subjected to maximal electroshock seizures (40 mA for 0.2 seconds) treatment. Alcoholic extract of leaves of H. tuberosus at the dose of 400 mg/kg significantly reduced the duration of hind limb extension and the protection of rats against maximal electroshock-induced seizures. The reference standards phenytoin (20 mg/kg) provided complete protection. Thus, the present study revealed an anticonvulsant effect of H. tuberosus against maximal electroshock-induced convulsions in rats.